Perilaku Konsumtif Generasi Z di Kota Kupang: Pengaruh Pendapatan, Media Sosial, dan Gaya Hidup - Anjelina Arabela Noni; Theresia Sanya Amanda Sasi; Gratia Tei Seran; Yohanes Pemandi Lian (Universitas 45 Surabaya, 2026)
This study aims to explore the consumptive behavior of Generation Z in Kupang City using a qualitative descriptive exploratory approach. The research focuses on three major influencing factors: income, social media, and lifestyle. Data were collected through in-depth interviews with 30 informants, two focus group discussions, and netnographic analysis of 20 TikTok and Instagram posts. The findings reveal that social media is the most dominant factor driving consumption through viral trends, influencer reviews, and algorithmic recommendations. FOMO and impulsive buying emerge as prominent behavioral patterns, strongly shaped by TikTok trends, flash sales, and peer influence. An aesthetic-oriented lifestyle further reinforces symbolic consumption, where products and activities serve as expressions of personal identity. Meanwhile, income functions only as a weak moderator; it limits spending capacity but does not reduce the desire to consume. The study concludes that Gen Z’s consumption is emotionally driven, digitally constructed, and closely tied to identity formation. These findings highlight the need for financial literacy strategies and digital education to help young consumers engage in more responsible consumption practices.